Ephaptic Coupling Is a Mechanism of Conduction Reserve During Reduced Gap Junction Coupling - Lin, Joyce; Abraham, Anand; George, Sharon A.; Greer-Short, Amara; Blair, Grace A.; Moreno, Angel; Alber, Bridget R.; Kay, Matthew W.; Poelzing, Steven (Frontiers in Physiology, 2022)
Many cardiac pathologies are associated with reduced gap junction (GJ) coupling, an important modulator of cardiac conduction velocity (CV). However, the relationship between phenotype and functional expression of the connexin GJ family of proteins is controversial. For example, a 50% reduction of GJ coupling has been shown to have little impact on myocardial CV due to a concept known as conduction reserve. This can be explained by the ephaptic coupling (EpC) theory whereby conduction is maintained by a combination of low GJ coupling and increased electrical fields generated in the sodium channel rich clefts between neighboring myocytes. At the same time, low GJ coupling may also increase intracellular charge accumulation within myocytes, resulting in a faster transmembrane potential rate of change during depolarization (dV/dt_max) that maintains macroscopic conduction. To provide insight into the prevalence of these two phenomena during pathological conditions, we investigated the relationship between EpC and charge accumulation within the setting of GJ remodeling using multicellular simulations and companion perfused mouse heart experiments. Conduction along a fiber of myocardial cells was simulated for a range of GJ conditions. The model incorporated intercellular variations, including GJ coupling conductance and distribution, cell-to-cell separation in the intercalated disc (perinexal width - WP), and variations in sodium channel distribution. Perfused heart studies having conditions analogous to those of the simulations were performed using wild type mice and mice heterozygous null for the connexin gene Gja1. With insight from simulations, the relative contributions of EpC and charge accumulation on action potential parameters and conduction velocities were analyzed. Both simulation and experimental results support a common conclusion that low GJ coupling decreases and narrowing WP increases the rate of the AP upstroke when sodium channels are densely expressed at the ends of myocytes, indicating that conduction reserve is more dependent on EpC than charge accumulation during GJ uncoupling.